2018
DOI: 10.21161/mjm.105317
|View full text |Cite
|
Sign up to set email alerts
|

Effectivity of Lactobacillus plantarum BSL against Listeria monocytogenes in rats

Abstract: Aims: To evaluate the effectivity of Lactobacillus plantarum BSL isolated from Indonesian sauerkraut against Listeria monocytogenes ATCC 7644 through in vitro and in vivo assay. Methodology and results: In vitro examination for antimicrobial activity against L. monocytogenes ATCC 7644 was performed using seven isolates of lactic acid bacteria (LAB). Lactobacillus plantarum BSL demonstrated the highest activity against L. monocytogenes and studied further in Sprague-Dawley (SD) rats. Treatment group of rats rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Other than that, L. plantarum B7 was able to reduce liver translocation and ameliorates histopathological lesions in rats infected by S. thphimurium (Tsai et al 2005), and then Acurcio et al (2017) also reported that administration of L. plantarum B7 significantly extent of ileal villi heights and number of hepatic inflammatory foci significantly lower than the control group. In addition, Meiyasa (2017) reported that treatment with L. plantarum BSL during nine-days could be able to reduce damage of liver and spleen in rats such as edema, necrosis, cell infiltration of lymphoid, proliferation of bile tract, vacuolization of hepatocytes cell for liver and depletion of lymphoid cells, extension of pulp area, and cell proliferation for spleen. Administration of L. plantarum BSL can reduce tissue damage of liver and spleen in rats possibly through mechanisms such as the production of antagonistic compounds and inhibitory substances, protective effects against pathogens (Acurcio et al 2017;Servin 2004;Prieto et al 2015 competition for nutrients or adhesion sites and/or immunomodulation (Bambirra et al 2007;Gibson et al 2005), cytokine production (Castanheira et al 2007), and reduces pro-inflammatory interleukin secretion (Puertollano et al 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other than that, L. plantarum B7 was able to reduce liver translocation and ameliorates histopathological lesions in rats infected by S. thphimurium (Tsai et al 2005), and then Acurcio et al (2017) also reported that administration of L. plantarum B7 significantly extent of ileal villi heights and number of hepatic inflammatory foci significantly lower than the control group. In addition, Meiyasa (2017) reported that treatment with L. plantarum BSL during nine-days could be able to reduce damage of liver and spleen in rats such as edema, necrosis, cell infiltration of lymphoid, proliferation of bile tract, vacuolization of hepatocytes cell for liver and depletion of lymphoid cells, extension of pulp area, and cell proliferation for spleen. Administration of L. plantarum BSL can reduce tissue damage of liver and spleen in rats possibly through mechanisms such as the production of antagonistic compounds and inhibitory substances, protective effects against pathogens (Acurcio et al 2017;Servin 2004;Prieto et al 2015 competition for nutrients or adhesion sites and/or immunomodulation (Bambirra et al 2007;Gibson et al 2005), cytokine production (Castanheira et al 2007), and reduces pro-inflammatory interleukin secretion (Puertollano et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…L. plantarum BSL was grown in MRS broth (Oxoid CM359) at 37 °C for 24 h, followed by pour plating in MRS agar (Oxoid CM361) incubated at 37 °C for 24-48 h for counting the bacterial cells. L. monocytogenes strain ATCC 7644 was cultured BHI broth (Oxoid CM1136) incubated at 37 °C for 24 h, and then counted in Listeria Selective Agar Base (Oxoid CM856), after incubation at 37 °C for 24-48 h (Meiyasa et al 2018).…”
Section: Bacterial Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Lactobacillus plantarum has capability in producing amylase, protease, and lipase enzymes as growth promoters (Sulistiani, 2017). L. plantarum bacteria can also produce lactic acid which modulates the immune responses, and produces plantaricin as an antimicrobial compound that can kill bacteria by disrupting the protein synthesis of pathogenic bacteria (Meiyasa et al, 2017). The demonstrations of many beneficial aspects produced by probiotic bacteria of Bacillus and L. plantarum and further combination of mixed cultures of both are expected to synergize with each other.…”
Section: Introductionmentioning
confidence: 99%